IMPACT OF SERVICE COSTS IN MANUFACTURING COST STRUCTURES - ANALYSIS OF CONTRACTS - Rodríguez Chávez, Agustín (2011)
With our article FLEXIBLE COST STRUCTURES TO OVERCOME THE GLOBALIZATION AND COMPETITIVENESS IN THE COMPANIES, presented in the journal QUIPUKAMAYOC Nº 33 we began an investigation to propose a model that incorporates the increasingly used strategy to achieve cost competitiveness in the market. Companies, with the new model of competitiveness that demands flexible production processes, are implementing business strategies in order to SPEED UP, SIMPLYFY and SECURE processes. Service companies are part of this strategy, which they are transferred functions or activities carried out within companies. But as we discussed in this article, SERVICE or OUTSOURCING costs can no longer be treated inside the other indirect costs of production (ICP) so we are looking for the fourth element, as a proposal to manage costs more accurately. This time, we will analyze various service contracts to understand because the costs associated with such strategies should be ACUMULATED, MEASURED and CONTROLLED as separately.